2012
DOI: 10.1029/2011ja017089
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of the cross‐shock electric potential at low Mach number, quasi‐perpendicular bow shock crossings using Cluster data

Abstract: .[1] The cross-shock electrostatic potential at the front of collision-less shocks plays a key role in the distribution of energy at the shock front. Multipoint measurements such as those provided by the Cluster II mission provide an ideal framework for the study of the cross-shock potential because of their ability to distinguish between temporal and spacial variations at the shock front. We present a statistical study of the cross-shock potential calculated for around 50 crossings of the terrestrial bow shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 47 publications
(50 reference statements)
3
63
0
Order By: Relevance
“…Previous observational [e.g., Wilson et al, 2007Wilson et al, , 2012 and simulation [e.g., Matsukiyo and Scholer, 2006;Muschietti and Lembège, 2013] studies only infer but do not quantify the importance of wave-particle interactions in the energy dissipation of collisionless shock waves. Other studies have focused on the effects due to quasi-static fields [e.g., Dimmock et al, 2012;Eastwood et al, 2007;Hull et al, 2001;Mitchell et al, 2012;Mitchell and Schwartz, 2014], arguing that wave-particle interactions are only of secondary importance. However, we have quantitatively shown that microscopic wave-particle interactions can regulate the macroscopic structure of low-to-mid Mach number collisionless shocks.…”
Section: Discussionmentioning
confidence: 99%
“…Previous observational [e.g., Wilson et al, 2007Wilson et al, , 2012 and simulation [e.g., Matsukiyo and Scholer, 2006;Muschietti and Lembège, 2013] studies only infer but do not quantify the importance of wave-particle interactions in the energy dissipation of collisionless shock waves. Other studies have focused on the effects due to quasi-static fields [e.g., Dimmock et al, 2012;Eastwood et al, 2007;Hull et al, 2001;Mitchell et al, 2012;Mitchell and Schwartz, 2014], arguing that wave-particle interactions are only of secondary importance. However, we have quantitatively shown that microscopic wave-particle interactions can regulate the macroscopic structure of low-to-mid Mach number collisionless shocks.…”
Section: Discussionmentioning
confidence: 99%
“…The value of the cross‐shock potential determines the energy loss by the directly transmitted ions and their eventual heating [ Gedalin , ]. It is of interest to compare the numerically found potential with the widely used model approximation [see, e.g., Dimmock et al ., ] φ=φmaxBBnormaluBmaxBnormalu.The comparison is shown in Figure . The adopted model appears to be very good at ion scales (larger than the electron ones).…”
Section: Numerical Modelingmentioning
confidence: 99%
“…A majority of these bursts occur at the shock ramp (when a clear ramp is identifiable). Though the waves are bursty, their amplitudes usually far exceed the typical few tens of mV/m quasi-static electric field component [Eastwood et al, 2007;Dimmock et al, 2012].…”
Section: Stereo and Wind Survey And Event Analysismentioning
confidence: 99%